Going to the dogs : greyhound racing, animal activism, and American popular culture - Thayer, Gwyneth Anne (Culture America., 2013)
A cultural history of greyhound racing in American, charting the sport's meteoric rise, and equally meteoric decline, against the backdrop of changes in American culture during the 20th century.